Influence Of Poster Media Health Disclosure On Knowledge Improvement In Tooth Brushing at SDN Wanajaya III, Telukjambe - Prisilia, Marcella; Harianti, Rini (Poltanesa, 2023)
Dental and oral disease is a public health problem today, especially periodontal tissue disease and dental caries. Both diseases can cause disruption to the masticatory function, which can interfere with the digestion and absorption of food. The Riskesdas 2018 data showed that the prevalence of dental and oral problems was 57.6% and that those receiving dental services were 10.2%. The prevalence of proper brushing behavior was 2.8%. This is due to a lack of knowledge about the importance of maintaining oral and dental health. The purpose of this study was to analyze the effect of health counseling with the use of poster media on increasing knowledge of brushing teeth. The type of research used is a quasi-experiment, using the one-group pre-post test design with a research target of 25 students in 3rd and 4th grade at SDN Wanajaya III. The results showed that most of the respondents were 9 years old, female and 4th grade students. Data analysis techniques using a paired sampled T-test. Paired sample T-test results show no significant results (p>0.05), which means that there is no significant increase in knowledge after health counseling activities with poster media. The value of knowledge before counseling was 2.36, and after counseling was 2.56. The difference between knowledge before and after counseling is 0.2, or only 8%. Further research needs to be done on other behavioral domains that can affect the habit of brushing teeth besides knowledge with the use of other health education media.